The Implementation of Good Agricultural Practices by Smallholder Oil Palm Farmers (Challenges and Determining Factors) - Novyandra Ilham Bahtera; Yulia Yulia; Herza Herza (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2025)
The palm oil industry in Indonesia, especially among smallholders, faces challenges in adopting Good Agricultural Practices (GAP) to achieve sustainability standards such as ISPO. This study explores the extent to which smallholders understand GAP and the factors that influence their adoption. Using a survey approach through structured interviews with oil palm farmers in Bangka District, this study explored the relationship between farmers' socio-economic characteristics and their understanding of GAP. The collected data were analyzed using multiple regression to identify significant patterns, especially regarding the influence of training and mentoring on GAP adoption. The study also highlighted unique dynamics between land size, income, and farming experience, providing important insights into small-scale farmers' adoption of modern methods. The results open up a discussion on how farmer capacity-building strategies can be designed to accelerate GAP adoption in the future.